Promising tomato hybrid Pusa Rakshit (DTPH-60) for cultivation under protected conditions - Yadav, R K; Tomar, B S; Husain, Zakir (Indian Horticulture, 2020)
Development of tomato hybrids/lines for protected condition will not only increase the productivity and quality of tomato but also make available the hybrid seeds at cheaper rate to the farmers’. At present the seed cost of private sector companies is very high and seed is sold on count basis. The newly developed tomato hybrid Pusa Rakshit (DTPH-60) thick pericarp, attractive round shape, red colour fruits and high yielding ability.